A preliminary cost-utility analysis of routine myasthenia gravis and thyroid dysfunction screening in acquired comitant Esotropia - Worapot Srimanan; Phawasutthi Keokajee; Sunita Sawangsribanterng (PLoS ONE, 2026)
This study evaluated the cost-effectiveness of routine screening for acetylcholine receptor antibody (AChR-Ab) and thyroid function tests (TFT) in patients with acquired comitant esotropia (ACE) without overt signs of myasthenia gravis (MG) or thyroid eye disease (TED). A retrospective cost–utility analysis was conducted in 110 patients at a Thai tertiary hospital between 2014 and 2024. A decision tree combined with a 10-year Markov model compared two strategies: no routine screening (symptom-triggered testing) and universal baseline screening with AChR-Ab and TFT. Costs were expressed in 2024 Thai Baht (THB) from a healthcare sector perspective, and outcomes were measured in quality-adjusted life years (QALYs). Model uncertainty was assessed using one-way sensitivity analyses and probabilistic sensitivity analysis with 10,000 simulations, incorporating downstream costs of follow-up, confirmatory evaluation, and treatment. In the base-case analysis incorporating real-world diagnostic accuracy, universal screening yielded higher QALYs (109.56 vs. 105.45) but also higher costs (฿2,826,680 vs. ฿1,653,500), resulting in an incremental cost-effectiveness ratio (ICER) of ฿285,360 per QALY gained. This exceeded Thailand’s willingness-to-pay threshold of ฿160,000–200,000 per QALY, indicating that universal screening was not cost-effective. Probabilistic sensitivity analysis showed that most simulations were located in the northeast quadrant of the cost-effectiveness plane, reflecting greater effectiveness with higher cost, with many exceeding the willingness-to-pay threshold. Key drivers included MG prevalence, utility loss from undiagnosed MG, and AChR-Ab test cost. TFT screening contributed minimal benefit due to the very low prevalence of thyroid dysfunction. Universal AChR-Ab screening may improve early detection of MG in ACE, but it was not cost-effective under current assumptions. Exploratory targeted screening appeared relatively more efficient, and symptom-triggered thyroid testing may be a more appropriate approach. These findings are preliminary and require validation in larger studies.